Self Concept and Career Planning Among Vocational Students: Konsep Diri dan Perencanaan Karier di Kalangan Siswa Kejuruan - Annisa Safira Amrosafitri; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Career planning represents a crucial developmental task for vocational high school students as they prepare for transition into the workforce. Specific Background: Many vocational students still demonstrate limited readiness in structuring realistic career plans, which may be associated with internal psychological factors such as self concept. Knowledge Gap: Although prior studies have examined self concept and career maturity, limited empirical evidence is available regarding their association within specific vocational school contexts. Aims: This study aims to determine the relationship between self concept and career planning among vocational high school students. Results: The findings indicate a positive and significant correlation between self concept and career planning, showing that students with stronger self perceptions tend to demonstrate more structured and directed career plans. Novelty: The study provides contextual empirical evidence from vocational students, reinforcing the psychological dimension of career planning within secondary education settings. Implications: These results highlight the importance of guidance and counseling programs that foster positive self concept development to support systematic career planning among vocational students. Keywords: Self Concept, Career Planning, Vocational Students, Career Development, Guidance And Counseling Key Findings Highlights Positive association identified between personal self perception and structured occupational preparation Students with stronger internal appraisal demonstrate clearer vocational direction School counseling context supports psychological determinants of future occupational readiness